WAYS OF INCREASING STUDENT TALKING TIME (STT) - Agustiana, Erika (LPPM STKIP PGRI Bandar Lampung, 2014)
Teachers talk in the classroom when they give instructions, provide feedback, ask questions to elicit information and when they giveexplanations. Students on the other hand talk when they answer questions, prepare for a speaking task, perform a speaking task, asking questions and of course when side-talking to friends. During different sections of a lesson, more or less teacher talk is appropriate because he/she will need to speak more to explain the concept and give examples.